Personal librarian programs in medical and academic health sciences libraries: a preliminary study. - Williams, Natasha Audrey (Journal of the Medical Library Association, 2022)
Objective: This preliminary study examined how personal librarian programs are implemented within medical and academic health sciences libraries. Increasing awareness of these programs and how they are implemented could create a larger and more accessible knowledge base for establishing best practices that similar libraries can look to when creating their own programs. Methods: To characterize existing programs, a twenty-two-item survey was sent to MEDLIB-L, AAHSL-ALL, ARCL-HSIG, and PSS-Lists email listservs in October 2018 to reach a broad audience of medical and academic health sciences librarians. Survey responses were analyzed using Qualtrics and Excel. Results: Of the 2,882 potential email recipients, 49 survey sessions were recorded, and a total of 38 survey sessions were completed (1.3% response rate). Of the 38 completed responses, representatives of 12 libraries (31.5%) reported that a personal librarian program had been implemented at their institution. For implementation, eight libraries involved 1--5 librarians, and four involved 6--10. Librarians were assigned 50--100 (n=6), 101--150 (n=1), or 151 or more (n=1) students each. The identified programs served medical students (n=11), nursing students (n=7), health professions students (n=7), dental students (n=2), and students in other fields (n=4). Services provided and communication methods were also identified. Conclusions: The personal librarian programs identified by the survey were uniquely structured to best meet the needs of their users, though similarities in implementation existed across institutions. Medical and academic health sciences libraries can look to these libraries as practical examples when starting their own personal library programs.